Molecular and Kinetic Characterization of Two Extracellular Xylanases Isolated from Leucoagaricus gongylophorus - Moreira, Ariele C.; Ferreira, Douglas; Almeida, Fernando G. de; Rodrigues-Filho, Edson; Fernandes, Joao B.; Silva, Maria F. G. F.; Vieira, Paulo C.; Pagnocca, Fernando C. [UNESP]; Souza, Dulce Helena F. (Humana Press Inc, 2014)
In this work, the xylanolytic profile of Leucoagaricus gongylophorus was studied, and two extracellular enzymes with xylanolytic activity (XyLg1 and XyLg2) were isolated, purified, and characterized. XyLg1 has a molecular mass of about 38 kDa and pI greater than 4.8. For beechwood xylan substrate, XyLg1 showed an optimum temperature of 40 A degrees C, optimum pH between 8.5 and 10.5, and Km = 14.7 A +/- 7.6 mg mL(-1). Kinetic studies of the XyLg1 using polygalacturonic acid as substrate were developed, and the enzyme showed optimum pH 5.5, optimum temperature between 50 and 60 A degrees C, and Km = 2.2 A +/- 0.5 mg mL(-1). XyLg2 has molecular weight of about 24 kDa and pI less than 4.8, and thus is an acid protein. Parameters such as optimum temperature (70 A degrees C) and pH (4.0), as well as the kinetic parameters (Km = 7.4 A +/- 2.0 mg mL(-1)) using beechwood xylan as substrate, were determined for XyLg2. This enzyme has no activity for polygalacturonic acid as substrate. XyLg1 and XyLg2 are the first native xylanases isolated and characterized from L. gongylophorus fungi and, due to their biochemistry and kinetic features, they have potential to be used in biotechnological processes.
Keywords: Xylanases; Leucoagaricus gongylophorus; Enzyme kinetic; Thermophilic enzyme